Face Longevity Risk: A Design of Government-issue Longevity Bond - Li, Tian (2007)
I, Tian Li, hereby declare that this dissertation and the work described in it is my own work, and was carried out in accordance with the regulations of the University of Nottingham, UK. The work is original except, where indicated by special references and citations in the text and no part of the dissertation has been submitted for any other degree.